Girl archaeologist : sisterhood in a sexist profession - Kehoe, Alice Beck, 1934- (University of Nebraska Press, 2022)
"Girl Archaeologist illuminates the life and trailblazing career of Alice Kehoe, a woman with a family who was always, also, an archaeologist"--